Error bound analysis and singularly perturbed Abel-Volterra equations - Angelina M. Bijura (Journal of Applied Mathematics)
Asymptotic solutions of nonlinear singularly perturbed Volterra integral equations with kernels possessing integrable singularity are investigated using singular perturbation methods and the Mellin transform technique. In particular, it is demonstrated that the formal approximation is asymptotically valid.